FARMERS' CAPACITY IMPROVEMENT THROUGH ORGANIC FARMING INTERVENTIONS - Padmaningrum, Dwiningtyas; Suminah; Widiyanti, Emi; Ihsaniyati, Hanifah; Utami, Bekti Wahyu; Hasan, Nugroho; Sujatmiko, Tri (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2025)
Dynamic and sustainable agricultural technology innovation is very important to increase production and the added value of agricultural products. This program aims to implement organic farming conversion on the Rojolele Srinuk rice variety, a javanica rice variety that has been modified to have advantages such as a shorter lifespan and resistance to pests. The program is carried out in five stages: (1) Program preparation, including planning and mapping targets; (2) Training in making organic fertilizer, through lectures and direct practice; (3) Practicing organic cultivation of Rojolele Srinuk rice on 2 hectares of land, using half the dose of chemical fertilizer and organic fertilizer; (4) Regular assistance to monitor and deal with obstacles such as pest attacks; (5) Farming bookkeeping training to optimize cost and profit management. Preparation for the program was carried out from May to June 2024, with training on June 21, 2024. Even though there was a rat pest attack that damaged up to 80% of the land, the use of botanical pesticides resulting from the training helped reduce the damage and allowed a harvest with a yield of 30-50% of the expected. Bookkeeping training increases farmers' understanding of cost and profit analysis. The final evaluation shows the potential and challenges of organic farming conversion that need to be addressed in future programs.